EWOM CREDIBILITY, TRUST, PERCEIVED RISK, AND PURCHASE INTENTION IN THE CONTEXT OF E-COMMERCE: MODERATING ROLE OF ONLINE SHOPPING EXPERIENCE - Amarullah, Dudi; Handriana, Tanti; Maharudin, Achmad (Fakultas Ekonomi dan Bisnis, UNTAN, 2022)
This study aimed to investigate the impact of eWOM credibility on trust and perceived risk and its effect on purchase intention with the online shopping experience as a moderator. The empirical data were collected from 247 e-commerce consumers in Indonesia through the distribution of online questionnaires. The PLS-SEM technique was applied to perform hypothesis testing. The results of this study showed that eWOM credibility has a positive and significant effect on consumer trust toward e-retailers and purchase intentions, but not on perceived risk. In addition, the results showed that consumer trust toward e-retailers has a positive and significant effect on purchase intention. Meanwhile, perceived risk has a negative and significant effect on purchase intention. Moreover, while online shopping experience positively moderated the relationship between perceived risk and purchase intention, online shopping experience did not moderate the relationship between consumer trust toward e-retailers and purchase intention. The findings of this study make a significant contribution both to business actors in e-commerce and to policymakers.JEL: M31.